International journal of music education (International Society for Music Education, 1983)
Beginning with vol. 22 (2004), each issue per volume has a special focus: the April issue focuses on "Research," the August issue, "Showcase" highlights topics of international interest, and the December issue, "Practice" deals with music teaching and learning at all age levels. Beginning with v. 26 (2008), issues are alternately called "Research" and "Practice."